PKM PENDAMPINGAN PENGENDALIAN INTERNAL PIUTANG MENGURANGI PIUTANG TAK TERTAGIH BAGI KARYAWAN PT ENSEVAL PUTERA MEGATRADING CABANG BOGOR - Rachman, Rachmawaty; Mulyadi, Mohammad Noorman (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
In facing competition and wanting to increase the number of sales, companies can sell their goods by credit to their customers. The existence of this credit sale will give rise to receivables (receivables), which will receive payment at maturity. The longer or longer the period for payment of receivables, will increase the period for collection of these receivables. Receivables are elements of working capital that are always rotating continuously, in which only one step is receivables turning into cash. The problem of accounts receivable is considered important in relation to the company, because the company must determine what the optimal amount of receivables is. Receivables must also manage efficiently related profits or additional profits obtained by changes in sales policies with expenses incurred due to receivables. Internal control systems include the organizational structure, and all coordinated methods and tools used within the company with the aim of maintaining the security of company assets, checking the accuracy and correctness of accounting data, promoting efficiency in operations and helping to maintain the management policies that have been adhered to previously set. . Keywords: Receivables, Internal Control